Pendekatan Kolaboratif Antara Guru Agama Dan Orang Tua Dalam Pendidikan Akhlak Siswa SMAN 1 Bandar Baru - Asman, Yunita; Rahmah, Husni; Muhammad, Muhammad (Program Studi Pendidikan Agama Islam, Universitas Muhammadiyah Bandung, 2024)
Teachers and parents play an important role in developing students' morals. Children's success really depends on parents and teachers in educating and developing them. This research aims to determine the forms of collaboration between religious teachers and parents in developing students' morals. This research uses a descriptive analysis method, namely describing and analyzing existing data. This research was carried out at SMAN 1 Bandar Baru, Pidie Jaya Regency with a sample size of 70 parents. Data collection techniques in this field research use questionnaires, observation, documentation and interviews. The results of the research show that the religious teachers and parents of students at SMAN 1 Bandar Baru have collaborated well, this can be seen from the forms of collaboration carried out by holding meetings and establishing good communication. The obstacles faced are due to parents being busy with daily activities, however, efforts are being made to overcome these obstacles by taking time away from daily activities, the majority of whom are farmers and fishermen.